2011
DOI: 10.1007/s13187-011-0233-z
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Short Acculturation Scale for Hispanics (SASH) Among Low-Income, Immigrant Hispanics

Abstract: The present analysis sought to determine the usefulness and validity of the Short Acculturation Scale for Hispanics (SASH) in assessment of acculturation among Hispanics participating in a colorectal cancer screening study. Primary data was collected from 2008 to 2009 through surveys in East Harlem community-based sites and health clinics among Hispanics. Bivariate correlations and independent samples t tests assessed SASH correlation with acculturation proxies and relationships between proxies, SASH, and soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
59
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(64 citation statements)
references
References 16 publications
2
59
0
Order By: Relevance
“…(26, 27) For Spanish-speaking Latinas, cultural values that govern social interactions and relationships with individuals perceived to be in positions of power, may influence their expectations of the patient-physician relationship and level of involvement in decision-making. (6, 14) Spanish-speaking Latinas may expect more direct guidance from their physicians during decision-making or may feel uncomfortable questioning their physicians.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(26, 27) For Spanish-speaking Latinas, cultural values that govern social interactions and relationships with individuals perceived to be in positions of power, may influence their expectations of the patient-physician relationship and level of involvement in decision-making. (6, 14) Spanish-speaking Latinas may expect more direct guidance from their physicians during decision-making or may feel uncomfortable questioning their physicians.…”
Section: Discussionmentioning
confidence: 99%
“…Study participants were also administered the Short Acculturation Scale for Latinos (SASH) which measures different aspects of language including spoken, thought, use at home and use with friends. (26, 27)…”
Section: Methodsmentioning
confidence: 99%
“…The survey collected basic demographic data, acculturation indicators such as place of birth, and language-based acculturation characteristics based on an adapted five-item language subscale of the Marin’s Short Acculturation Scale for Hispanics (SASH) [23]. The language subscale has demonstrated higher correlation with other acculturation indicators compared to the overall scale [24]. While the SASH has not been validated in the four other racial groups in this study, the SASH demonstrated reliability and validity when adapted for Korean [25] and Filipino immigrants in the US [26].…”
Section: Methodsmentioning
confidence: 99%
“…Sociodemographic and behavioral variables included as covariates were age, sex, marital status, Hispanic background, acculturation (using the Short Acculturation Scale for Hispanics [SASH] Language & Ethnic Social Relations Subscales [38]), education, yearly household income, family network size, alcohol consumption (drinks per week), smoking status (never, former, current), depressive symptoms (i.e., ten-item Center for Epidemiologic Studies Depression Scale; [39]), and perceived social support (i.e., Interpersonal Support Evaluation List; [40]).…”
Section: Methodsmentioning
confidence: 99%